2020
DOI: 10.1002/ijgo.13171
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up cervical cancer prevention in Western Kenya: Treatment access following a community‐based HPV testing approach

Abstract: Objective To evaluate access to treatment after community‐based HPV testing as testing within screen‐and‐treat programs has the potential to lower mortality from cervical cancer in low‐resource settings. Methods A prospective cohort study was conducted in western Kenya in 2018. Women aged 25–65 years underwent HPV self‐testing. HPV‐positive women were referred for cryotherapy. Participant data were obtained from questionnaires during screening and treatment. The proportion successfully accessing treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“… 9 In the 2018 global call for cervical cancer elimination, the WHO recommends HPV testing as a primary screening method, 10 listing it as a Best Buy for noncommunicable disease prevention. 11 HPV screening, although increasingly feasible through self-sampling, 12 is limited by poor specificity, as it cannot separate transient from persistent infections, leading to overtreatment in a screen-and-treat approach. 9 , 13 This lack of specificity highlights a need for adjunct screening or triage methods that increase specificity within the screen-and-treat approach without a substantial decrease in sensitivity or increase in cost or infrastructure requirements.…”
Section: Introductionmentioning
confidence: 99%
“… 9 In the 2018 global call for cervical cancer elimination, the WHO recommends HPV testing as a primary screening method, 10 listing it as a Best Buy for noncommunicable disease prevention. 11 HPV screening, although increasingly feasible through self-sampling, 12 is limited by poor specificity, as it cannot separate transient from persistent infections, leading to overtreatment in a screen-and-treat approach. 9 , 13 This lack of specificity highlights a need for adjunct screening or triage methods that increase specificity within the screen-and-treat approach without a substantial decrease in sensitivity or increase in cost or infrastructure requirements.…”
Section: Introductionmentioning
confidence: 99%
“…All women who tested positive for HPV, regardless of HIV status, were referred to one of three sub-county hospitals within a ten-kilometer radius for cryotherapy treatment, which was provided at no cost. Results of this follow-up strategy and treatment uptake have been previously published elsewhere [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed using Stata/MP version 17 (StataCorp). As previously mentioned, the analysis for linkage-to-treatment for women who tested positive for HPV is reported elsewhere [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Strategies to implement HPV testing as primary screening include community‐based interventions to increase coverage of screening, especially in rural areas where access to health facilities may be limited. Community health campaigns and home visits by community health workers in particular have been shown to increase screening uptake, especially when women are given the option to self‐collect samples for HPV testing 18‐24 . A study in Uganda found over 99% compliance among women who were offered HPV tests by self‐collection, whereas VIA at a health clinic reached only approximately 48% compliance, given that self‐collection allowed women to provide samples immediately upon recruitment by health workers at home or work visits 23 .…”
Section: Hpv Dna Testing As a Cervical Cancer Screening Method: Next ...mentioning
confidence: 99%
“…Among common HPV DNA test types (eg, careHPV, Hybrid Capture 2, Aptima, and Xpert DNA), processing usually occurs in batches and can take several hours after being transferred from the community screening site to the laboratory 39 . Treatment acquisition among HPV‐positive women thus remains inadequate; the proportion of screen‐positive women accessing care ranges from 32% to 60% among several community‐based cervical cancer screening interventions 18‐23 . In 1 study, implementing mobile treatment sites resulted in treatment rates as high as 86% among women notified, which involved stationing convenient treatment units within the community and moving from community to community to provide treatment for intervals of several days 20 .…”
Section: Hpv Dna Testing As a Cervical Cancer Screening Method: Next ...mentioning
confidence: 99%